2019
DOI: 10.1007/s13592-019-00684-x
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting the reproductive health of honey bee (Apis mellifera) drones—a review

Abstract: In the honey bee, Apis mellifera , colonies are composed of one queen, thousands of female workers, and a few thousand seasonal males (drones) that are reared only during the reproductive season when colony resources are plentiful. Despite their transient presence in the hive, drones have the important function of mating with virgin queens, transferring their colony's genes to their mates for the production of fertilized, worker-destined eggs. Therefore, factors affecting drone health and reproductive competen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(46 citation statements)
references
References 99 publications
(188 reference statements)
2
42
0
2
Order By: Relevance
“…An additional 13 publications providing data from bumble bee microcolony [ 14 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ], queenright colony [ 30 , 31 ] studies and relevant testing guidelines [ 32 , 33 ] were found by reviewing the reference section of [ 34 ]. Four publications providing background on honey bee males were also included in this review [ 20 , 35 , 36 , 37 ]. Publications discussed in this review are specifically focused on male bumble bee biology, their role within the nest, sensitivity to toxicants, immunity, mating behavior, reproductive measures, and their combined impact on queen success and colony viability ( Table 1 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…An additional 13 publications providing data from bumble bee microcolony [ 14 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ], queenright colony [ 30 , 31 ] studies and relevant testing guidelines [ 32 , 33 ] were found by reviewing the reference section of [ 34 ]. Four publications providing background on honey bee males were also included in this review [ 20 , 35 , 36 , 37 ]. Publications discussed in this review are specifically focused on male bumble bee biology, their role within the nest, sensitivity to toxicants, immunity, mating behavior, reproductive measures, and their combined impact on queen success and colony viability ( Table 1 ).…”
Section: Methodsmentioning
confidence: 99%
“…Currently, there are no accepted methods for assessing chronic toxicity or colony-level effects in bumble bees of any caste. While Apis bee researchers are beginning to recognize the importance of drones to colony reproductive health [37], bumble bee drones contribute far more to colony success than the act of insemination. Bumble bee drones are dynamic partners in the colony, making contributions to the genetic composition of the colony, maintaining brood nest temperature and, in stark contrast to honey bee drones, Bombus drones contribute directly to queen overwintering survival and by extension foundress activity.…”
Section: Risk Assessment Considerationsmentioning
confidence: 99%
“…The queen is a critical member of the honey bee colony, and her primary roles are prolific egg production and the release of pheromones that maintain social cohesion [8][9][10]. In addition to the queen's genetic make-up, queen quality-including health status and reproductive vigor-is a consequence of the nurse bees' care during development of the queen larva, the health and fertility of the~15 drones with which she mates, and the care she receives from worker bees in her colony after mating [11][12][13][14][15][16][17][18][19]. Simultaneously, queen health and reproductive capacity have direct impacts on the health, well-being, and vigor of the colony she is heading [8,20,21].…”
Section: Introductionmentioning
confidence: 99%
“…This reduction naturally occurs during the second stage of eversion of the endophallus and during the injection of semen into the lateral oviducts of the queen, and has been attributed to increased pressure on the sperm during these stages. The sperm viability may also vary according to drone age, nutrition, management practices, environmental factors and exposure to insecticides and miticides [105].…”
Section: Sperm Viability (Plasma Membrane Integrity)mentioning
confidence: 99%